A Small-Sized Population of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells Shows High Stemness Properties and Therapeutic Benefit - Miyeon Kim; Yun Kyung Bae; Soyoun Um; Ji Hye Kwon; Gee-Hye Kim; Soo Jin Choi; Wonil Oh; Hye Jin Jin (Stem Cells International)
Mesenchymal stem cells (MSCs) represent a promising means to promote tissue regeneration. However, the heterogeneity of MSCs impedes their use for regenerative medicine. Further investigation of this phenotype is required to develop cell therapies with improved clinical efficacy. Here, a small-sized population of human umbilical cord blood-derived MSCs (UCB-MSCs) was isolated using a filter and centrifuge system to analyze its stem cell characteristics. Consequently, this population showed higher cell growth and lower senescence. Additionally, it exhibited diverse stem cell properties including differentiation, stemness, and adhesion, as compared to those of the population before isolation. Using cell surface protein array or sorting analysis, both EGFR and CD49f were identified as markers associated with the small-sized population. Accordingly, suppression of these surface proteins abolished the superior characteristics of this population. Moreover, compared to that with large or nonisolated populations, the small-sized population showed greater therapeutic efficacy by promoting the engraftment potential of infused cells and reducing lung damage in an emphysema mouse model. Therefore, the isolation of this small-sized population of UCB-MSCs could be a simple and effective way to enhance the efficacy of cell therapy.